Four‐dimensional echocardiographic and pathologic findings of congenital left ventricular aneurysm: A case report. Issue 1 (26th June 2020) - Wen, Yanting; Xiang, Guishuang; Zhang, Jing; Lai, Qiancheng; Zhang, Li
Abstract : The sonographic and histopathologic features of a rare case of left ventricular aneurysm are reported, detailing the method of prenatal diagnosis and suggesting possible etiology of congenital ventricular aneurysm.